IMPORTANCE AND ANALYSIS OF INVESTMENTS IN SECURITIES IN THE FORMATION OF THE RESOURCE BASE OF COMMERCIAL BANKS. - Dustmurodova Sarvinoz Habib kizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article contains thoughts and opinions about the impact of securities investment on the formation of the resource base of commercial banks and its current analysis.